Family Background and School Achievement of Children with Motoric Disorders - Jasmina Radojlovic; Danijela Ilic-Stosovic; Nela Djonovic; Tatjana Simovic (Journal of Education in Science, Environment and Health)
There is no pedagogical literature about school achievement that does not include the family as a very important factor. Family and family relationships of children with motoric disorders are determined by the ability of parents and other family members to build an objective attitude toward the child with disability. That includes the construction priority in the development of the child. The main aim of this paper is to provide information about possible correlation between various family backgrounds of children with motoric disorders and their school achievement. The family background is defined by several general and specific pedagogical aspects. General aspects of the family background are related to the socio – economic status. Special pedagogical characteristics are related to parents interest in school achievements of their children, parens' help with the child learning (defined through the school curriculum), parent’s involving in forcing studying habits and their support in exploring children social surrounding. Participants in this research were 75 parents all with children with motoric disorders in one school for education of children with different forms of disability. The survey used in this study was designed by the researchers. The results show that there is no correlation between economic conditions of family and school achievement of children with motoric disorders. There is a correlation between school achievement and  educational status of parents, marital status of parents, parental assistance in homework, encouraging child to learn when child is coping with some difficulties at school, ensuring consistency in learning and conversation between parents and child on various topics.